"To See is to Believe?"—Modernization and U.S.–China Exchanges in the 1970s. (2nd January 2016) - Lin, Mao
Abstract : This article discusses U.S.–China "people-to-people" exchanges, an important yet less studied aspect of U.S.–China relations during the 1970s. Moving away from the narrative that emphasizes strategic calculations by policy makers in both countries, this paper covers the cultural exchange programs sponsored by non-state actors such as the National Committee on U.S.–China relations. It argues that the bilateral exchanges produced a discursive construction of China's modernization, which both consolidated Sino-American strategic cooperation and helped reshape China's modernization efforts. By concentrating on how those exchanges strengthened the ties between China and the United States, this article fills an important gap in the current scholarship and tries to provide a fuller understanding of U.S.–China rapprochement in the 1970s.